Integrative transcriptome analysis identifies deregulated microRNA-transcription factor networks in lung adenocarcinoma - Cinegaglia, Naiara C. [UNESP]; Andrade, Sonia Cristina S.; Tokar, Tomas; Pinheiro, Maísa [UNESP]; Severino, Fábio E. [UNESP]; Oliveira, Rogério A. [UNESP]; Hasimoto, Erica N. [UNESP]; Cataneo, Daniele C. [UNESP]; Cataneo, Antônio J.M. [UNESP]; Defaveri, Júlio [UNESP]; Souza, Cristiano P. [UNESP]; Márques, Marcia M.C.; et al. (Impact Journals, 2016)
Herein, we aimed at identifying global transcriptome microRNA (miRNA) changes and miRNA target genes in lung adenocarcinoma. Samples were selected as training (N = 24) and independent validation (N = 34) sets. Tissues were microdissected to obtain >90% tumor or normal lung cells, subjected to miRNA transcriptome sequencing and TaqMan quantitative PCR validation. We further integrated our data with published miRNA and mRNA expression datasets across 1,491 lung adenocarcinoma and 455 normal lung samples. We identified known and novel, significantly over- and underexpressed (p ≤ 0.01 and FDR ≤ 0.1) miRNAs in lung adenocarcinoma compared to normal lung tissue: let-7a, miR-10a, miR-15b, miR-23b, miR-26a, miR-26b, miR-29a, miR-30e, miR-99a, miR-146b, miR-181b, miR-181c, miR-421, miR-181a, miR-574 and miR-1247. Validated miRNAs included let-7a-2, let-7a-3, miR-15b, miR-21, miR-155 and miR-200b; higher levels of miR-21 expression were associated with lower patient survival (p = 0.042). We identified a regulatory network including miR-15b and miR- 155, and transcription factors with prognostic value in lung cancer. Our findings may contribute to the development of treatment strategies in lung adenocarcinoma.
Keywords: Lung adenocarcinoma; MicroRNAs; Molecular targets; Transcription factor networks; Transcriptome sequencing